2012
DOI: 10.1371/journal.pone.0037524
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Sensory Abnormalities in Patients with Unilateral Neuropathic Pain; A Quantitative Sensory Testing (QST) Study

Abstract: In patients who experience unilateral chronic pain, abnormal sensory perception at the non-painful side has been reported. Contralateral sensory changes in these patients have been given little attention, possibly because they are regarded as clinically irrelevant. Still, bilateral sensory changes in these patients could become clinically relevant if they challenge the correct identification of their sensory dysfunction in terms of hyperalgesia and allodynia. Therefore, we have used the standardized quantitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 37 publications
2
44
0
Order By: Relevance
“…There is ample preclinical (Tal and Bennett, 1994;Malan et al, 2000), human experimental (Shenker et al, 2008), and clinical (Konopka et al, 2012) evidence that for neuropathic-like conditions the signs and symptoms (sensory abnormalities) can extend into regions beyond those directly innervated by the injured nerve. This emphasises that there may be no non-affected control site in a chronic pain patient.…”
Section: Experimental Assessment Of Central Sensitisationmentioning
confidence: 99%
See 1 more Smart Citation
“…There is ample preclinical (Tal and Bennett, 1994;Malan et al, 2000), human experimental (Shenker et al, 2008), and clinical (Konopka et al, 2012) evidence that for neuropathic-like conditions the signs and symptoms (sensory abnormalities) can extend into regions beyond those directly innervated by the injured nerve. This emphasises that there may be no non-affected control site in a chronic pain patient.…”
Section: Experimental Assessment Of Central Sensitisationmentioning
confidence: 99%
“…Use of the standardised QST protocol of the German Research Network on Neuropathic Pain has revealed abnormality for some sensory parameters at the non-affected side that was as high as 57%; this indicates that bilateral sensory dysfunction in patients with unilateral neuropathic pain is more the rule than the exception (Konopka et al, 2012) and often very minimal sensory differences exist between affected and non-affected areas (Geber et al, 2011). Studies of thermal sensory function at the affected and non-affected side of acute and chronic complex regional pain syndrome patients have shown bilateral sensory changes as well (Huge et al, 2008).…”
Section: Localised and Widespread Hyperalgesiamentioning
confidence: 99%
“…Clinically, bilateral presentation of pain symptoms occurred in about 5-15 % of patients with complex regional pain syndrome [93,94]. There is abundant clinical evidence that the signs and symptoms extend into regions beyond those directly innervated by the injured nerve in neuropathic conditions [95,96]. Patients with second-degree burns can develop sensory abnormalities involving the contralateral, uninjured side of the body [97].…”
Section: Extraterritorial Spreading Sensitizationmentioning
confidence: 99%
“…Contralateral mirror-imaging has been experimentally demonstrated in a variety of injuries in laboratory animals: inflammatory cutaneous and joint (reviewed in Shenker et al 2003), inflammatory and non-inflammatory muscle Radhakrishnan et al 2003) and neuropathic (reviewed in Koltzenburg et al 1999). Altered contralateral sensory perception after unilateral injury or in chronic pain syndromes is reported as well in clinics (Huge et al 2008;de la Llave-Rincón et al 2009;Fernández-de-las-Peñas et al 2009;Konopka et al 2012;Werner et al 2013). However, the frequency of this disorder in humans is not known.…”
Section: Introductionmentioning
confidence: 98%